Sains dalam perspektif Islam: Implementasi integrasi sains dan teknologi dalam dunia pendidikan - Fuadati, Ifrokhatul (Maliki Interdisciplinary Journal, 2024)
Science and religion are two things that go hand and hand with each other. But people often think that science and religion are something different, which cannot be put together. Whereas in essence both are something that is interconnected. Integration is one of alternatives that can bridge between science and religion so thaht there is no confusion of arguments that assume that science and religion are something different.